From Voyager-IRIS to Cassini-CIRS: Interannual variability in Saturn's stratosphere? - Sinclair, J; Irwin, P; Fletcher, L; Greathouse, T; Guerlet, S; Hurley, J; Merlet, C (2014)
We present an intercomparison of Saturn's stratosphere between Voyager 1-IRIS observations in 1980 and Cassini-CIRS observations in 2009 and 2010. Over a saturnian year (~29.5. years) has now passed since the Voyager flybys of Saturn in 1980/1981. Cassini observations in 2009/2010 capture Saturn in the same season as Voyager observations (just after the vernal equinox) but one year later. Any differences in Saturn's atmospheric properties implied by a comparison of these two datasets could therefore reveal the extent of interannual variability. We retrieve temperature and stratospheric acetylene and ethane concentrations from Voyager 1-IRIS (δν̃=4.3cm-1) observations in 1980 and Cassini-CIRS (δν̃=15.5cm-1) 'FIRMAP' observations in 2009 and 2010. We observe a difference in temperature at the equator of 7.1. ±. 1.2. K at the 2.1-mbar level that implies that the two datasets have captured Saturn's semiannual oscillation (SSAO) in a slightly different phase suggesting that its period is more quasi-semiannual. Elevated concentrations of acetylene at 25°S in 1980 with respect to 2010 imply stronger downwelling at the former date which may also be explained by a difference in the phase of the SSAO and its dynamical forcing at low latitudes. At high-southern and high-northern latitudes, stratospheric temperatures and hydrocarbon concentrations appear elevated in 1980 with respect to 2009/2010. This could be an artefact of the low signal-to-noise ratio of the corresponding observations but might also be explained by increased auroral activity during solar maximum in 1980. © 2014 Elsevier Inc.